PENGARUH ENVIRONMENTAL, SOCIAL, DAN GOVERNANCE (ESG) TERHADAP KINERJA PERUSAHAAN DENGAN VARIABEL MODERASI BOARD SIZE - Tanjaya, Felix; Ratmono, Dwi (Diponegoro Journal of Accounting, 2024)
The purpose of this study is to examine the impact of ESG performance and the subcomponents of ESG on firm’s performance and the impact of board size on the relation between ESG performance on firm’s performance. The dependent variable used in this study is firm’s performances which the indicators of firm’s performances are return on asset, return on equity, and Tobin’s Q. ESG performance and the subcomponents of ESG are used as the independent variables. Furthermore, this study used board size as a moderating variable. The sample in this study consist of 375 companies that had ESG score on the Bloomberg’s database in the period of 2018-2022. The data that used in this study was secondary data and selected by using purposive sampling method. The technique of the analysis data used in this study was multiple regression analysis for examining the hypothesis.Based on the empirical results of this study show that the ESG performance has no impact on firm’s performance by full data and before Covid-19. ESG performance has positive impact on ROA and ROE during Covid-19 This study also found that there has no association of board size between ESG performance and firm’s  performance.